A multicriteria methodology for estimating consumer acceptance of alternative powertrain technologies - Sousa, Nuno (2019)
A multicriteria methodology for estimating consumer acceptance of vehicles with alternative powertrain technologies is presented. The approach is based on the non-compensatory ELECTRE TRI method and compares hybrid, plug-in hybrid, and electric vehicles to conventional models. Criteria considered are ownership costs and restrictions to vehicle use, which apply mainly to electric vehicles. The methodology is applied to a case study of 94 vehicles of different market segments and alternative powertrains. The analysis is carried out per segment and considers two driver profiles, city and all-purpose, and a baseline scenario for all cases. Output is tested for statistical significance, with powertrain technology as disaggregating factor, and a sensitivity analysis on the base scenario is also carried out, as well as a comparison with results derived by a compensatory multicriteria method (TOPSIS). Results show that conventional vehicles are the top choice for the small vehicles segment, due to lower purchase prices and higher use flexibility. For medium sized vehicles, all powertrain technologies are competitive for city drivers, whereas for all-purpose drivers, use restrictions for electric vehicles make these less attractive. The baseline scenario and sensitivity analysis highlight that opting for an electric vehicle depends strongly on the driver's use flexibility needs. As such, an electric vehicle can be either very attractive or outright unusable, regardless of financial considerations. It is also seen that plug-in hybrids do not present any significant advantage, as compared to other, non-electric choices, due to their higher purchase prices.